2016
DOI: 10.1111/jcpt.12440
|View full text |Cite
|
Sign up to set email alerts
|

Review of drug utilization patterns in NICUs worldwide

Abstract: Summary What is known and objectives When considering acute care settings, such as the neonatal intensive care unit (NICU), the inappropriate use of medicines poses a great risk to vulnerable babies at the start of their lives. However, there is limited published literature that explores the current medication management practices in NICUs and where the main misuse issues lie. Therefore, the purpose of this review was to give an overview of medicine use in NICUs worldwide and identify therapeutic areas requiri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
65
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(74 citation statements)
references
References 48 publications
6
65
1
2
Order By: Relevance
“…Our results on most used classes of drugs (antimicrobials, cardiovascular agents, analgesics and respiratory drugs) are in accordance to other studies investigating the profile of drug use in NICUs, performed in other Western Countries [5, 1012]. …”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our results on most used classes of drugs (antimicrobials, cardiovascular agents, analgesics and respiratory drugs) are in accordance to other studies investigating the profile of drug use in NICUs, performed in other Western Countries [5, 1012]. …”
Section: Discussionsupporting
confidence: 91%
“…For instance, in the first postnatal period, neonatologists often have to manage respiratory distress syndrome, patent ductus arteriosus (PDA), necrotizing enterocolitis (NEC) and other infections [1]. At present, very little is known on the actual use of combination of drugs in neonatal intensive care settings and their safety; studies investigating drug use in the neonatal population usually focused on single active substances and their status in terms of unauthorized or off-label use [25]. The evidence gathered so far however highlighted increased susceptibility of babies to drug-related toxicity (especially, renal damage [2]).…”
Section: Introductionmentioning
confidence: 99%
“…We demonstrated that drugs for alimentary tract were by far most commonly used mainly due to high prescription rate of vitamins and probiotics similarly shown in previous studies [1].…”
Section: Discussionsupporting
confidence: 80%
“…Medicines play a pivotal role in improving neonatal health and reducing mortality, and thus are widely used in neonatal units. A median of 3 to 11 drugs per neonate are given depending on the setting and gestational age (GA) [1,2]. Most drugs administered to neonates are either offlabel or unlicensed and the exposure of off-label/unlicensed drugs is the highest among preterms [1].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation